2015
DOI: 10.1371/journal.pone.0123756
|View full text |Cite
|
Sign up to set email alerts
|

Human Umbilical Cord Matrix Mesenchymal Stem Cells Suppress the Growth of Breast Cancer by Expression of Tumor Suppressor Genes

Abstract: Human and rat umbilical cord matrix mesenchymal stem cells (UCMSC) possess the ability to control the growth of breast carcinoma cells. Comparative analyses of two types of UCMSC suggest that rat UCMSC-dependent growth regulation is significantly stronger than that of human UCMSC. Their different tumoricidal abilities were clarified by analyzing gene expression profiles in the two types of UCMSC. Microarray analysis revealed differential gene expression between untreated naïve UCMSC and those co-cultured with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…It is known that growth of cancer cells under 3D culture mimics tumor growth in vivo more than that under 2D culture conditions. 16 For this reason, 3D culture methods such as spheroid assays 16,17,[30][31][32][33] have been applied for the evaluation and screening of novel therapeutics for cancer treatments. In the present study, CMF treatment alone attenuated the growth of CT26 cells in both 2D culture ( Figure 2A) and a spheroid assay (Figure 3A and B).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that growth of cancer cells under 3D culture mimics tumor growth in vivo more than that under 2D culture conditions. 16 For this reason, 3D culture methods such as spheroid assays 16,17,[30][31][32][33] have been applied for the evaluation and screening of novel therapeutics for cancer treatments. In the present study, CMF treatment alone attenuated the growth of CT26 cells in both 2D culture ( Figure 2A) and a spheroid assay (Figure 3A and B).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that 3D culture condition more closely mimics natural tumor growth than that in 2D culture condition [34]. For this reason, 3D culture methods such as clonogenic assay [4244] and spheroid assay [34] have been applied to the evaluation and screening of novel therapeutics for cancer treatments. Present study results, therefore, may suggest that the cytotoxic antitumor effect of PCEPS alone is not strong enough to inhibit 3D spheroid growth of CT26 cells within a short time.…”
Section: Discussionmentioning
confidence: 99%
“…I.V administration of MSCs can effectively inhibit tumor cell proliferation and inhibition of metastasis [19]. Also, it was reported that the MSCs isolated from human and rat umbilical cord could significantly suppress growth of breast cancer cells in vitro and in vivo [43][44][45].…”
Section: Discussionmentioning
confidence: 99%